Awareness of Physical Therapy among Different Medical Professionals - Sabahat Ali, Hafiza Rabia Javed, Kashaf Khan, Hira Shahid, Faiza Hanif, Farwa Batool, Zarwa Mansoor (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To put efforts into promoting awareness about physical therapy in the specified population. Study design: It was an observational study. Place and duration: The duration of study was 6 months and was carried out at Farooq Clinic Khushab. Methodology: An observational study was conducted among medical professionals and was based on a cross-sectional study that was carried out with the help of self-structured questionnaire. Results: 63% of the house officers are well-aware of physical therapy and have sufficient knowledge about it. Some medical professionals including cardiologists and orthopedic surgeons said that physical therapy has now become a very important part of the quality health and well-being of patients. Conclusion: Physical therapy plays a very essential role in enhancing and improving the standards of health. All medical professionals of different fields should have knowledge and awareness about physical therapy for helping people to manage and improve their problems with the help of different therapies. Keywords: Physical Therapy, Medical Officers, Awareness, Knowledge